Improved Potato Breeds using Recombinant Technology - K Pattnaik, Ajoy; Mahapatra, P (International Journal of Psychosocial Rehabilitation, 2025)
Potato is the third most significant global non-cereal crop, with nearly 400 million tons produced every year worldwide and which in general, represents a non-fattening, nutritious and wholesome food. It is a vigorously managed crop which requires irrigation, fertilization and many other applications for the highest yield possible. The potato tubers consist of variable amounts of carbohydrates, minerals, vitamin C, essential amino acids, etc. and are the major staple food in many developing countries. Significant characteristics are easily found in the members of wild potato, but conventional breeding can take 15-20 years to implement. This is due to the fact that certain wild species are sexually incompatible, which desires to exclude the unwanted species from adapted germplasms, and have difficulties in identifying widely applicable molecular markers. All these aspects have diverted the scientific attention to the nutritional value of the potato by keeping the yield unaffected. Several experimental studies have demonstrated the improved nutritional value of the potato tubers. Moreover, potato is one of the crops which are facing great losses due to many pests and diseases and some of them causing too much loss of the product. Since, most of the quality traits of the potato are genetically controlled, so the breeding technology can surely meet the requirements of the good quality of potato yield. The recombinant technology of breeding potato for the good quality traits requires a continuous flow of new genes and their diversity into the gene of Solanum tuberosum (potato).